Protocolo para avaliar a acessibilidade ao computador para alunos com paralisia cerebral - Lourenço, Gerusa Ferreira (2008)
The national and the foreigner literature indicate that the successful education of students with cerebral palsy can require the implementation of resources and appropriate equipments, allowing the individual to improve their performance and complete daily tasks in a more efficient and independent way. The assistive technology is a term used to name the equipments / resources as well as the services linked to them that promote to the individual a greater success in the accomplishment of activities, increasing, maintaining or improving their functional capacities. The implementation of those resources is a complex process, involving variables of the person, of the equipment, of the task to be executed and of the environment. An appropriate initial evaluation is of great importance and the current study had as objective to systematize a tool with specific procedures to verify the eligibility of computational resources of high assistive technology to the students with cerebral paralysis to be applied by a team of special education and rehabilitation professionals. It is a descriptive research, based in a North American checklist already existent that evaluates the physical characteristics and posture to determine the best way to use the computer. The methodology involved phases as the translation and the cross-cultural adaptation of that checklist as well as the implementation of a supplemental guide for additional use of the referred checklist for the educational context. The translation procedures, theoretical and technical adaptation of the North American checklist and theoretical analysis (content and semantics) were accomplished with the participation of special education specialist professionals as judges. With the analysis of the judges' results, the outcome indicated the relevance of the translated checklist s proposition together with the itinerary built to the professionals' reality involved in the education of children with cerebral palsy. The study resulted in a protocol for computer accessibility evaluation, in which there are five parts, the first three were created (Student Identification, Performance in the Classroom Academic Activities, Interest in the Computer s Implementation) and the last two adapted from the translated checklist (PCA: Physical Characteristics Assessment Computer Access for Individuals with Cerebral Palsy and Conclusions). The theoretical validation phase should be accomplished before the checklists are made available, and it is expected that the presented study will contribute to the process of making viable a checklist for the evaluation and the prescription of resources of high assistive technology that allows the computer access and, in that way, improves the education quality for those students. Besides, it seeks a contribution to the practice of professionals that work on that theme when making available that kind of checklist, collaborating on the theoretical development of this area in the Brazilian reality